Synthesis, structural characterization and biological activities of new organotin (iv) complexes with n (4)- substituted thiosemicarbazone/hydrazone ligands containing nns/ons/on donor atoms - Md. Abdus, Salam (Universiti Malaysia Sarawak, (UNIMAS), 2012)
In the course of research, the synthesis, structural characterization and biological activities of new tin(IV)/organotin(IV) complexes obtained from substituted thiosemicarbazone/hydrazone ligands have been undertaken. The structures of these synthesized compounds were elucidated by elemental analyses, molar conductivity, UV-Vis, FT-IR, ¹H and ¹³c NMR spectral studies. The molecular structures were also established by X-ray single crystal diffraction analyses.